Sustainable bio energy: the potential of Ni-Fe/NZA as a catalyst for pyrolysis of sugarcane bagasse waste (Saccharum officinarum L.) for bio-oil production - Muhammad Hafiz Tanjung; Anisya Larasaty; R. Fikry Nanda Habibie; Assyifa Aini Ilmi; Sutan Badarudin Sufi; Syaiful Bahri; Muhammad Imam Nugraha (Konversi, 2024)
The depletion of fossil fuels and the increase in greenhouse gas emissions have sparked public concern. Along with the problems occurred, the need for energy continues to increase, while energy source reserves are decreasing. This research was conducted with an aim to determine the effect of the addition of Ni-Fe/NZA catalyst on bio-oil yield from the pyrolysis process of sugarcane bagasse waste. Chemical analysis was carried out using GC-MS instrument and physical analysis was carried out using a pycnometer, viscometer, pH meter, and bomb calorimeter. The results showed that the bio-oil produced had better quality as evidenced by a series of chemical and physical analysis, so bio-oil can be used as a renewable alternative fuel with dominant compounds in the form of furfural and acetic acid. The highest bio-oil yield was obtained at 1% catalyst weight percentage and at the temperature of 400℃ of 48.1%. The density of bio-oil had a range of 0.93-1.01 gr/mL, bio-oil viscosity ranged from 25.75-30.01 cP and Bio-oil pH ranged from 2.62-3.27. The fastest first drop of bio-oil was obtained at 105℃. The calorific value had a range of 20.26-27.05 MJ/kg. It can then be concluded that Ni-Fe/NZA has great potential as a catalyst in the pyrolysis process and improves the quality of bio-oil produced in the development of sustainable technology.